Cancer Control Programs in East Asia: Evidence From the International Literature - Malcolm A. Moore (Korean Society for Preventive Medicine, 2014)
Cancer is a major cause of mortality and morbidity throughout the world, including the countries of North-East and South-East Asia. Assessment of burden through cancer registration, determination of risk and protective factors, early detection and screening, clinical practice, interventions for example in vaccination, tobacco cessation efforts and palliative care all should be included in comprehensive cancer control programs. The degree to which this is possible naturally depends on the resources available at local, national and international levels. The present review concerns elements of cancer control programs established in China, Taiwan, Korea, and Japan in North-East Asia, Viet Nam, Thailand, Malaysia, and Indonesia as representative larger countries of South-East Asia for comparison, using the published literature as a guide. While major advances have been made, there are still areas which need more attention, especially in South-East Asia, and international cooperation is essential if standard guidelines are to be generated to allow effective cancer control efforts throughout the Far East.